3‐Chloro‐2‐hydroxypropyl Dimethyl Dehydroabietyl Ammonium Chloride: Synthesis, Characterization, and Physicochemical Properties. Issue 3 (1st May 2013) - Pei, Li‐jun; Cai, Zhao‐sheng; Song, Zhan‐qian; Zhu, Xue‐mei; Shang, Shi‐bin
Abstract: 3‐Chloro‐2‐hydroxypropyl dimethyl dehydroabietyl ammonium chloride (CHPDMDHA) was synthesized from dehydroabietylamine (DHA) and epichlorodrin. The synthesis was done in three steps. First, DHA was transformed into N, N ‐dimethyl dehydroabietyl amine (DMDHA) through Eschweiler‐Clarke Reaction. Second, the DMDHA was reacted with hydrochloric acid and translated into DMDHA hydrochloride. Third, the CHPDMDHA was obtained after the DMDHA hydrochloride had reacted with epichlorodrin and recrystallized using a solvent composed of ethyl acetate and ethanol. The critical micelle concentrations (CMC) of CHPDMDHA at 25 °C was found to be 2.56 × 10 −4 mol L −1, and its surface tension at the CMC (γCMC ) was determined to be 27.4 mN m −1 ; these data suggest that the surface activities of CHPDMDHA are better than those of benzalkonium chloride (BC), so that CHPDMDHA could be used as a good alternative to BC.